Impoliteness Used By Haters on Instagram Comments of Federation Internationale De Football Association (FIFA) - Nico Wikang Tri Diatma; Agus Wijayanto (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research describes the types of impoliteness strategies and emotional expressions in impoliteness used by haters in commenting on Instagram social media. Many impolite stattements were deployed by haters of FIFA because this football association is considered unfair in making decisions and treating Israel and Russia differently. Descriptive qualitative method was employed to analyze the research data. The present research took data from haters’ comments in the comment column of the @fifa Instagram account. The data analysis included identifying and describing the use of impoliteness strategies and emotional expressions involved the impoliteness. The research has revealed that some types of impoliteness strategies were used by the haters with Bald on record impoliteness being the most dominant strategy and anger was the most dominant emotional expression involved in the impoliteness.